2020
DOI: 10.3390/ijms21155329
|View full text |Cite
|
Sign up to set email alerts
|

RORγ Structural Plasticity and Druggability

Abstract: Retinoic acid receptor-related orphan receptor γ (RORγ) is a transcription factor regulating the expression of the pro-inflammatory cytokine IL-17 in human T helper 17 (Th17) cells. Activating RORγ can induce multiple IL-17-mediated autoimmune diseases but may also be useful for anticancer therapy. Its deep immunological functions make RORɣ an attractive drug target. Over 100 crystal structures have been published describing atomic interactions between RORɣ and agonists and inverse agonists. In this review, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…RORγt played a vital role in driving Th17 cell differentiation and IL-17 production, which indicated in the pathology of multiple autoimmune and inflammatory diseases [ 7 , 20 , 21 ]. However, currently reported drugs targeting RORγt cannot be applied in clinical practice due to the side effects, poor therapeutic action and off-target effect [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RORγt played a vital role in driving Th17 cell differentiation and IL-17 production, which indicated in the pathology of multiple autoimmune and inflammatory diseases [ 7 , 20 , 21 ]. However, currently reported drugs targeting RORγt cannot be applied in clinical practice due to the side effects, poor therapeutic action and off-target effect [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that RORγt promoted IL-17A production and Th17 polarization. It also taken part in antitumor immunity, autoimmune diseases as well as transplant rejection [ 6 , 7 ]. Based on structural analysis, RORγt regulated target gene expression and physiological function through interacting with both coactivators and corepressors.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure a, the RORγ LBD X-ray cocrystal structure and binding interactions of the pyrazinone fragment 20 is overlaid with the X-ray crystal structure of the second-generation indoline 21 . While compound 20 does not extend far enough into the binding pocket to reach the Arg367 anchor, it does appear to fill the lower portion of the binding pocket well; this partial occupation may explain the weak RORγ RGA activity of compound 20 that has been previously observed . The core ring system of compound 20 does not overlay well with compound 21 ; however, it functions as a scaffold to position key peripheral groups in the correct trajectories.…”
mentioning
confidence: 83%
“…The concept of an agonist lock originates from the His479-Tyr502-Phe506 cluster, which is critical for the agonism and inverse agonism of RORγt binding in both the orthosteric site pocket and the allosteric site pocket. In the business end, His479 forms π–π interactions with Tyr502 and Phe506 on H12, and it also forms hydrogen bonds with Tyr502 (Figure ).…”
Section: What Is the Agonist Lock In Rorγt?mentioning
confidence: 99%